Severe postherpetic neuralgia and facial paralysis in the oral and periauricular regions managed with acupuncture and electroacupuncture: a case report - Li, Junlong; Wang, Jing; Li, Guiping; Zhang, Jieying; Zhang, Boru; Wang, Shu (Frontiers in Pain Research, 2024)
Postherpetic neuralgia (PHN) is a severe and persistent pain condition following herpes zoster infection. This case report details the analgesic effects of acupuncture combined with electroacupuncture in a 66-year-old male patient presenting with PHN and peripheral facial paralysis, who showed limited response to conventional treatment with corticosteroids and antiviral medications. Following a comprehensive treatment protocol, including pricking-cupping bloodletting, and targeted acupuncture, the patient experienced significant pain relief and improved facial nerve function. This report highlights the potential of traditional Chinese medicine (TCM) in managing PHN, with sustained improvement observed over a one-year follow-up period.